2000
DOI: 10.1038/sj.onc.1203317
|View full text |Cite
|
Sign up to set email alerts
|

HYAL1LUCA-1, a candidate tumor suppressor gene on chromosome 3p21.3, is inactivated in head and neck squamous cell carcinomas by aberrant splicing of pre-mRNA

Abstract: The hyaluronidase ®rst isolated from human plasma, Hyal-1, is expressed in many somatic tissues. The Hyal-1 gene, HYAL1, also known as LUCA-1, maps to chromosome 3p21.3 within a candidate tumor suppressor gene locus de®ned by homozygous deletions and by functional tumor suppressor activity. Hemizygosity in this region occurs in many malignancies, including squamous cell carcinomas of the head and neck. We have investigated whether cell lines derived from such malignancies expressed Hyal-1 activity, using norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 27 publications
(22 reference statements)
2
41
0
2
Order By: Relevance
“…However, because HYAL1 (and also HYAL2 and HYAL3) is present on chromosome 3p 21.3 locus, and this region is a critical tumor homozygous deletion region in lung and breast cancers, it has been suggested that HYAL1 may be a tumor suppressor (7,49). A recent study clearly demonstrates that the RASSF1 gene and not HYAL1 is the tumor suppressor gene present in that locus (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, because HYAL1 (and also HYAL2 and HYAL3) is present on chromosome 3p 21.3 locus, and this region is a critical tumor homozygous deletion region in lung and breast cancers, it has been suggested that HYAL1 may be a tumor suppressor (7,49). A recent study clearly demonstrates that the RASSF1 gene and not HYAL1 is the tumor suppressor gene present in that locus (50).…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronidases would then qualify as candidate tumor suppressor gene products but no frequent inactivating mutations were identified so far. However, another inactivating mechanism was suggested and demonstrated in some oral cancers (Frost et al, 2000). The unusually large 5' UTR, found by PCR, indicated the presence of a retained intron.…”
Section: Hyal1mentioning
confidence: 99%
“…We showed recently that HYAL1 expression in radical prostatectomy specimens is an independent predictor of biochemical recurrence in prostate cancer patients (27,34). In tumor cells, the expression of enzymatically active HYAL1 seems to be regulated by alternative mRNA splicing (35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%